Thioxanthone-Diphenyl Anthracene: Visible Light Photoinitiator - Balta, Demet Karaca; Temel, Gokhan; Goksu, Gokce; Ocal, Nuket; Arsu, Nergis (AMER CHEMICAL SOC, 2012)
7,12-Diphenyl-14H-naphto[2,3-b]thioxanthen-14-one (TX-DPA) was synthesized and characterized as a potential visible light photoinitiator for radical polymerization. TX-DPA has an excellent absorption character in the visible region and the photophysical properties of TX-DPA were investigated by fluorescence and laser flash photolysis studies and the photopolymerization of methyl methacrylate in air atmosphere helped to understand the initiation mechanism of TX-DPA. Moreover, it is possible that the production of singlet oxygen from the quenching of (3)TX-DPA by molecular oxygen resulted in the reaction of singlet oxygen with TX-DPA to form an endopercaide: decomposition of endoperoxide leads to initiating radicals.
Keywords: FREE-RADICAL POLYMERIZATION; 4-ALKYLAMINO BENZOPHENONE INITIATORS; LASER FLASH-PHOTOLYSIS; DOUBLE CLICK REACTIONS; COINITIATOR AMINE; CHAIN THIOXANTHONE; SINGLET OXYGEN; PHOTOPOLYMERIZATION; WATER; PHOTOCHEMISTRY; Polymer Science